A comparative study between ultrasonography guided classical interscalene block plus superficial cervical plexus block versus low approach interscalene block plus superficial cervical plexus block in lateral one-third of clavicle and proximal humerus surgery - Biswas, Rajasree; Mondal, Priyanka; Nandy, Sabyasachi (Asian Journal of Medical Sciences, 2022)
Background: Classical interscalene approach of brachial plexus block with superficial cervical plexus block has become the anesthetic technique of choice in the upper arm, shoulder, and clavicle surgery but there is high risk of complications and sparing of C8-T1 nerve roots. Here, we used low approach of interscalene block (ISB) with superficial cervical plexus block for lateral one-third of clavicle and proximal humerus surgeries. Previously, none of the study compare ultrasonography (USG) guided low ISB (LISB) to the conventional approach for lateral one-third of clavicle and proximal humerus surgeries. Aims and Objectives: The aim of the study was to compare onset, duration, density of sensory-motor block, and severity of complication between ISB and LISB with superficial cervical plexus block. Materials and Methods: Patients with fracture of lateral end of clavicle and proximal humerus of 18–60 years of 324, American Society of Anesthesiologists I and II patients, were randomly assigned into two groups ISBS and LISB with superficial cervical plexus block (LISBS) to find out the difference in density of sensory-motor blockade associated with any complications between two groups. Results: The degree of the ulnar block after 5 and 15 min was found to be 2.8±2.6 and 1.1±1.8 in LISBS, respectively, for ISBS 3.0±1.5 and 1.8±2.0, respectively, based on a ten-point scale. After 15 min, motor block occurred in the median nerve in 151 patients out of 162 (92.8%), and in all of the other three nerves in all 162 patients. Horner syndrome and hoarseness were less frequent in LISB with superficial cervical plexus block patients than in ISB with superficial cervical plexus block patients (P=0.0009 and 0.003, respectively) which was statistically significant. Conclusion: The present study confirmed the achievement of an appropriate sensory and motor block in the lateral one-third of clavicle with proximal humerus surgery, including the ulnar nerve with no complications than ISB.